Elections in Azerbaijan: Political infighting and strategic interests of great powers - El'chan E. Nuriev (Stiftung Wissenschaft und Politik (SWP), 2005)
Two years after being elected President of the Republic of Azerbaijan, Ilham Aliyev finds himself facing a mounting domestic political crisis. In the parliamentary election held on 6 November 2005, both the opposition and Western election observers recorded serious procedural violations and instances of election fraud. The government continues to maintain that all the conditions for fair, transparent, and democratic elections were fulfilled. After all, international organisations had made efforts to ensure that this was the case well in advance of the elections themselves. The United States, the most important external player in the region, let it be known that any attempt to tamper with the elections would prompt an unequivocal response on its part. But whereas international attention paid to the elections has focussed on the power struggles between the government and opposition forces, the dynamics within the ruling elite should not be neglected. Indeed, in the run-up to the elections, clear fault lines had formed within the government camp. (SWP Comments / SWP)
Keywords: 320